Dissipation of Knowledge and the Boundaries of the Multinational Enterprise - Valeria Gattai (Fondazione Eni Enrico Mattei (FEEM), 2005)
This paper provides a theoretical formalisation of the joint-venture contract, as an alternative to Foreign Direct Investment (FDI), within a Dissipation of Intangible Assets framework. In a two-period model, we discuss how the threat of knowledge spillover shapes the boundaries of a Multinational Enterprise. Similarly to the theoretical findings on the FDI-licensing trade off, we show that the integrated solution is more likely to emerge when know-how easily spills over i.e. when firms are endowed with more Intangible Assets or they belong to high tech industries. Probit estimates, from a new firm-level dataset, show that Japanese manufacturing operations in Europe are in line with these predictions.
Keywords: F23; C25; O5; 330; Dissipation; Intangible assets; FDI; joint-venture; Internalisation; Japan; Joint Venture; Direktinvestition; Immaterielles Anlagevermögen; Wissenstransfer; Multinationales Unternehmen; Japan